2018
DOI: 10.51744/cip12
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and gap map of studies assessing the effectiveness of interventions for people with disabilities

Abstract: This report summarises findings from an evidence and gap map (EGM) commissioned by the Department for International Development (DFID) and undertaken by the Campbell Collaboration (Campbell) and the International Centre for Evidence and Disability (ICED). An EGM is a table which offers a visual presentation of the available evidence for a particular sector. The map provides an overview of what studies are available, but it does not summarise the findings. In the disability map the rows are intervention categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…In all, the focus is on children Other more topic-specific rigorous reviews have been conducted and reported in the peer-reviewed literature (Buysse & Bailey, 1993;Elbaum et al, 1999;Forlin et al, 2013;Gersten et al, 2001;Hudson et al, 2013;Katz & Mirenda, 2002;Paradise et al, 2009;Pierce et al, 2004;Purdie et al, 2002;Reichrath et al, 2010;Ruijs & Peetsma, 2009;Trout et al, 2003;. Reid (Pierce et al, 2004)); and/or -Out of date (Buysse & Bailey, 1993;Elbaum et al, 1999;Trout et al, 2003) Finally, White et al (2018) conducted an evidence gap map (EGM)-which can be distinguished from a review in that it is used to identify, map and describe existing evidence of effectiveness studies and highlight gaps in evidence base, and can inform later systematic reviews-on interventions for people with disabilities in LMIC. Their EGM included impact evaluation and systematic reviews assessing the effect of interventions for people with disabilities and their families/carers in LMICs.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, the focus is on children Other more topic-specific rigorous reviews have been conducted and reported in the peer-reviewed literature (Buysse & Bailey, 1993;Elbaum et al, 1999;Forlin et al, 2013;Gersten et al, 2001;Hudson et al, 2013;Katz & Mirenda, 2002;Paradise et al, 2009;Pierce et al, 2004;Purdie et al, 2002;Reichrath et al, 2010;Ruijs & Peetsma, 2009;Trout et al, 2003;. Reid (Pierce et al, 2004)); and/or -Out of date (Buysse & Bailey, 1993;Elbaum et al, 1999;Trout et al, 2003) Finally, White et al (2018) conducted an evidence gap map (EGM)-which can be distinguished from a review in that it is used to identify, map and describe existing evidence of effectiveness studies and highlight gaps in evidence base, and can inform later systematic reviews-on interventions for people with disabilities in LMIC. Their EGM included impact evaluation and systematic reviews assessing the effect of interventions for people with disabilities and their families/carers in LMICs.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…Finally, White et al (2018) conducted an evidence gap map (EGM)—which can be distinguished from a review in that it is used to identify, map and describe existing evidence of effectiveness studies and highlight gaps in evidence base, and can inform later systematic reviews—on interventions for people with disabilities in LMIC. Their EGM included impact evaluation and systematic reviews assessing the effect of interventions for people with disabilities and their families/carers in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…-Case management approaches: theories of change or intervention logics that inform how interventions are delivered. These can be implicit or explicit (White et al, 2021).…”
Section: The Interventionmentioning
confidence: 99%
“…Youth participation in offending, anti‐social and violent behaviour is a significant cause of concern. There has been a significant increase in serious violence, as well as the number of knife‐related crimes committed by children in recent years (White et al, 2021). Youth violence is the fourth leading cause of death for young people worldwide, with an estimated 200,000 deaths per year (World Health Organization, 2015).…”
Section: Introductionmentioning
confidence: 99%